Type I interferon-mediated autoinflammation and autoimmunity. (December 2017) - Kretschmer, Stefanie; Lee-Kirsch, Min Ae
Highlights: Cell-intrinsic constitutive activation of type I interferon (IFN) can cause autoinflammation. Autoimmunity requires additional cell-extrinsic cues by the adaptive immune system. Intracellular nucleic acid waste management is important for immune homeostasis. DNA damage can cause cGAS-dependent type I IFN activation. Inhibition of constitutive type I IFN activation is a promising therapeutic approach. Abstract : The monogenic type I interferonopathies comprise a heterogenous group of disorders of the innate immune system associated with constitutive activation of antiviral type I interferon (IFN). Despite a remarkable phenotypic diversity, type I interferonopathies are commonly characterized by autoinflammation and varying degrees of autoimmunity or immunodeficiency. The elucidation of the underlying genetic causes has revealed novel cell-intrinsic mechanisms that protect the organism against inappropriate immune recognition of self nucleic acids by cytosolic sensors such as cGAS or MDA5 through metabolizing or processing of intracellular DNA or RNA. What emerges from these findings is a more integrated picture of the different modes by which unabated type I IFN causes autoinflammation or drives autoimmunity.